Overview of Slovenian Control Programmes for Selected Cattle Diseases, Listed Under Category C, D or E of the European Animal Health Law - Hodnik, Jaka Jakob; Knific, Tanja; Starič, Jože; Toplak, Ivan; Ocepek, Matjaž; Hostnik, Peter; Ježek, Jožica (Frontiers in Veterinary Science, 2021)
The European Union (EU) regulates the control of cattle diseases listed in categories A and B of the Animal Health Law (AHL). However, the control of other cattle diseases that have no, or limited EU regulation, is left to each member state. Slovenia has five control programmes (CPs) for non-EU regulated cattle diseases: bovine viral diarrhoea (BVD), infectious bovine rhinotracheitis (IBR), enzootic bovine leukosis (EBL), bluetongue and anthrax. Two (IBR and BVD) are voluntary and the others (EBL, anthrax and bluetongue) are compulsory. The three compulsory CPs are funded by the government. All the CPs are run by the government and laboratory tests are performed by the National Veterinary Institute. The rules for the CPs are laid down in Slovenian legislation. In addition, there is a national directive for the control of salmonellosis. Both BVD and IBR are endemic and have CPs based on increased biosecurity, testing and culling or vaccination, financed by the animal owners. Slovenia has been officially free of EBL since 2005 and carries out surveillance based on serological testing of a representative number of herds and inspection of carcasses at slaughter or necropsy. Vaccination is the main disease control measure for anthrax (sporadic) and bluetongue (currently perceived free – vaccination since 2017). Lack of motivation of farmers to participate in voluntary disease CPs and to implement and follow strict biosecurity measures are the most pressing issues in improving the health status of Slovenian cattle. An overview of the existing CPs and the circumstances leading to their implementation are presented.